Effect of temperature on glass-ceramic films prepared by impregnation of commercial float glass surfaces with oxide powders under pressure - Cava, S.; Sequinel, T.; Tebcherani, S. M.; Lazaro, S. R.; Pianaro, S. A.; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2010)
SnO(2) samples were prepared as ultrafine powder by a chemical synthesis method and deposited on the surface of commercial float glass substrates The glass surface was impregnated with these powders under high gas pressure (1.6-1.8 MPa) and heating to below the glass transition temperature in a designed pressurized chamber, forming SnO(2) films on glass surface Phases were analyzed by X-ray diffraction and the results confirmed the SnO(2) powders as a single-phase tetragonal structure. Analysis of the chemical composition of glass substrates before and after powder impregnation revealed an ion exchange process caused by the substitution of sodium ions by tin ions on the glass surface. Differences in the surface morphology of SnO(2) films on glass surface were related to the morphology of synthesized powders for deposition and impregnation. The mechanism of SnO(2) films on glass surface was based on mass transfer between the glass substrates and SnO(2) powders as a function of the treatment temperature. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Films; Inclusions; Microstructure-final; Glass-ceramics; Pressure impregnation